Cream Formulation of Ethanol Extract of Banana Peel (Musa Paradisiaca Var. Sapientum (L)) - Idarwati Duha; Adek Chan (Jurnal Dunia Farmasi, 2016)
Introduction: Musa Paradisiaca Var. Sapientum (L) or know as the banana plants in Indonesia is a herbaceous plants that belongs to the family Musaceaa. Objective: This Study Aims tho determine the rind of banana  (Musa Paradisiaca Var. Sapientum (L)) can be formulated in Cream.Methode: This research the conducted experimental, the sample is extracted by maceration using 70% ethanol. Extract later in pekatkan at temperatrs 400C with a pressure of 100 atm. Viscous extract obtained of used at an concentration of 5%, 10% and 15%. Results: Results showed that banana peel extract can be prepared as a cream and meet the pyshical Evaluation of the stocks. Homogeneity  test result that  the preparation made sufficiently homogeneous, pH 6.5 to 6.9 is obtained cream still meet the skin’s Ph ranging between 6.0 to 7.0 and cream type test. Colculsion: Dosage formulations cream bark ethanol extract banana (Musa Paradisiaca Var. Sapientum (L)) qualified physical evaluation preparations include homogeneity, pH test dan thest type cream.